2023
DOI: 10.1001/jamanetworkopen.2023.0394
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Aggressive End-of-Life Care Among Older Adults With Metastatic Cancer Living in Nursing Homes and Community Settings

Abstract: ImportanceNearly 10% of the 1.5 million persons residing in nursing homes (NHs) have received or will receive a diagnosis of cancer. Although aggressive end-of-life (EOL) care is common among community-dwelling patients with cancer, little is known about such patterns of care among NH residents with cancer.ObjectiveTo compare markers of aggressive EOL care between older adults with metastatic cancer who are NH residents and their community-dwelling counterparts.Design, Setting, and ParticipantsThis cohort stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…Various studies have explored the patterns of care at the EOL in older patients with cancer [ 21 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 ]. All these studies report high rates of healthcare utilization that increase at late stages of life, and some even report aggressive and excessive EOL care [ 35 , 40 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various studies have explored the patterns of care at the EOL in older patients with cancer [ 21 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 ]. All these studies report high rates of healthcare utilization that increase at late stages of life, and some even report aggressive and excessive EOL care [ 35 , 40 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have explored the patterns of care at the EOL in older patients with cancer [ 21 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 ]. All these studies report high rates of healthcare utilization that increase at late stages of life, and some even report aggressive and excessive EOL care [ 35 , 40 , 43 ]. In studies comparing older patients with cancer to the general older population, high rates of hospitalizations, medicine use and clinician visits in EOL are especially prevalent in the former [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review on the extent of non-beneficial treatments in acute hospitals at the end of life confirmed widespread occurrence [47]. And despite increased emphasis to reduce inappropriate end-of-life care in the past decade, a recent large population-based study among more than 146,000 persons aged 66 years and older with advanced cancer demonstrated such care remains very common [48]. Several randomised and matched controlled trials have demonstrated that the integration of specialist palliative care into oncology care leads to improved quality of life and more appropriate end-of-life care for patients with advanced cancer [9][10][11].…”
Section: Discussionmentioning
confidence: 99%
“…Research has consistently demonstrated a rise in healthcare service utilization during the final months of life [18][19][20][21]. However, there remains a need to fully understand the key variables that affect service utilization, including types of care at end-of-life.…”
Section: Introductionmentioning
confidence: 99%